Partisipasi Umat dalam Pelayanan Doa-Doa di Lingkungan Maria Bunda Allah Peniwen Stasi Ngrejo - Anjeli Sarma; Lorens Goa (Pusat Riset dan Inovasi Nasional, 2025)
This study contains a motivation and needs required by Catholics in neighborhood prayer, one of which is the neighborhood of Mary Mother of God Peniwen. This research was raised because the situation in the neighborhood where many people still find it difficult to participate in leading prayers such as: Word Service, Deepening of Faith, Rosary, and many other prayers. One of the reasons why people have not been able to lead or participate in prayer services in the neighborhood is because they are still hesitant to appear in front of many people, are still afraid of making mistakes, and some have abilities in that field but do not participate in serving duties. So, the purpose of this study is to help describe the real situation experienced by some people in the neighborhood regarding their participation and service in neighborhood prayer. This study uses observation methods and direct interviews in the neighborhood, and is also assisted by many sources from other scientific works. From the results of using this method, the researcher also learned what causes or what reasons so that people have not been able to lead or participate in prayer services in the neighborhood or station. From that, the researcher conducted prayer training needed for the congregation. This will enable the congregation to understand their shortcomings and what God needs to foster and realize participation in prayer ministry in their communities. Hopefully, the results of this research will inspire many congregations to participate in prayer ministry in their communities.